Frontal brain activity assessment during basic life support skill acquisition and transfer in serious game based learning environments - Mehmet Emin Aksoy; Mert Deniz Polat; Patricia A. Shewokis; Dilek Kitapcioglu; Tuba Usseli; Atahan Agrali; Serhat Ilgaz Yöner; Kurtulus Izzetoglu (PLoS ONE, 2026)
Basic Life Support (BLS) is a crucial life-saving skill, and the effectiveness of different training methods for acquiring and transferring BLS knowledge and skills remains an important area of investigation. Traditional methods, such as lectures, may be less engaging and lack the practical application necessary for optimal skill transfer. New training modalities, including serious games on tablets and in virtual reality (VR) environments, offer interactive experiences, enable personalized feedback, and repetitive practice, potentially enhancing the learning process. However, the effectiveness of these newer training delivery methods on skill acquisition, transfer, and the underlying neurophysiological mechanisms needs further investigation. Hence, this study explores the effectiveness of various BLS training modalities, including traditional lecture-based instruction, tablet-based serious gaming, and VR-based serious gaming. A wearable functional near-infrared spectroscopy (fNIRS) sensory system is used to monitor prefrontal cortex (PFC) activity during training and subsequent hands-on testing. A total of 51 participants, who were randomly assigned to one of three training groups (lecture, tablet, VR), were analyzed. These participants underwent fNIRS monitoring during the training sessions and a final hands-on exam. Our findings revealed that while all three training modalities led to comparable hands-on exam performance, there were notable differences in neural activation patterns. VR-based training appeared to elicit neural responses indicative of more efficient use of cognitive resources during the hands-on test, suggesting its potential effectiveness as a practice mode for skill acquisition and transfer. These findings highlight the importance of considering both behavioral and neurophysiological metrics when assessing the efficacy of educational interventions.